Serum bilirubin levels on ICU admission are associated with ARDS development and mortality in sepsis. Issue 9 (28th May 2009) - Zhai, R; Sheu, C C; Su, L; Gong, M N; Tejera, P; Chen, F; Wang, Z; Convery, M P; Thompson, B T; Christiani, D C
Abstract : Background: Hyperbilirubinaemia is a common complication of sepsis. Elevated bilirubin may induce inflammation and apoptosis. It was hypothesised that increased serum bilirubin on Intensive Care Unit (ICU) admission contributes to sepsis-related acute respiratory distress syndrome (ARDS). Methods: Serum bilirubin on ICU admission was measured in 1006 patients with sepsis. Serial serum bilirubin was analysed prospectively in patients with sepsis who had ARDS for a period of 28 days. The effects of clinical factors and variants of the UGT1A1 gene on serum bilirubin levels were determined. Outcomes were ARDS risk and mortality. Results: During 60-day follow-up, 326 patients with sepsis developed ARDS, of whom 144 died from ARDS. The hyperbilirubinaemia (⩾2.0 mg/dl) rate in patients with ARDS (22.4%) was higher than in those without ARDS (14.1%, p = 0.002). For each 1.0 mg/dl increase in admission bilirubin, ARDS risk and 28- and 60-day ARDS mortalities were increased by 7% (OR = 1.07; p = 0.003), 20% (OR = 1.20; p = 0.002) and 18% (OR = 1.18; p = 0.004), respectively. Compared with subjects with bilirubin levels <2.0 mg/dl, patients with hyperbilirubinaemia had higher risks of ARDS (OR = 2.12; p = 0.0007) and 28-day (OR = 2.24; p = 0.020) and 60-day ARDS mortalities (OR = 2.09; p = 0.020). In sepsis-related ARDS, serial bilirubin levels in non-survivors were consistently higher than in survivors (p<0.0001). Clinical variables explained 29.5% of the interindividual variation in bilirubin levels, whereas genetic variants of UGT1A1 contributed 7.5%. Conclusion: In sepsis, a higher serum bilirubin level on ICU admission is associated with subsequent ARDS development and mortality.